Associations of early-life exposures and socioeconomic status with cognitive development at preadolescence - Wasef Na'amnih; Ashraf Akawi; Ahmad Abu-Moch; Rinat Cohen; Gal Dror; Eias Kassem; Khitam Muhsen; Asher Ornoy (Elsevier, 2023)
Background: The long-term relations of socioeconomic status (SES) and early-life exposures with cognitive development at preadolescence are not fully understood, especially in low SES populations. We examined associations of SES and early-life exposures including feeding practices, physical growth and infections with cognitive development among preadolescents from underprivileged communities. Methods: A prospective study was conducted among 146 healthy children from two relatively low SES Arab villages in Israel, who were recruited at age 1-9 weeks and followed until age 18 months. Information was obtained on their feeding practices, health status and growth indicators. Cognitive development at age 10-12 years was assessed using the Wechsler Intelligence Scale, including the full-scale intelligence quotient (FSIQ) and scores of four cognitive domains. Multiple linear regression models were performed. Results: Nearly all the children (98%) were breastfed in infancy. Bivariate correlations were found of SES, growth indices and rates of diarrheal and respiratory illnesses in infancy, but not of feeding practices, with cognitive scores. In multivariable models, SES was positively (p < 0.001) associated with all the cognitive domains (beta coefficient ranges 4.3 to 8.2). Birthweight was positively associated with FSIQ (p = 0.039) and the perceptual reasoning index (p = 0.002). Weight for age Z score at age 10-14 months was positively associated with the verbal comprehension index (p = 0.003). The rate of respiratory illnesses was negatively associated with the perceptual reasoning index (p = 0.05). Conclusion: SES is strongly associated with cognitive development even in relatively low SES communities. Birthweight, weight indicators and respiratory illness in infancy might affect cognitive development through preadolescence.